A Detailed Review on Quantum Computing Technologies - Saravanamoorthi, P. (Recent Research Reviews Journal, 2022)
Modern computing approaches like quantum computing are based on the remarkable occurrences of quantum mechanics. It is a combination of information theory, computer science, mathematics, and physics. The study of quantum computing includes the design and development of computer-based technologies based on quantum theory, which explains the nature and behaviour of energy and matter at atomic and sub-atomic levels. Sub-atomic particles such as electrons and photons are used in quantum computing. These particles exist in two different states (i.e., 1 and 0) based on quantum bits or qubits. Compared to conventional computers, quantum computing offers higher computing capacity, lower energy utilization, and high speed. This article reviews the state-of-the-art quantum computing technologies and different ways in which the qubits can exponentially increase the efficiency of quantum computers and sort various possibilities and identify potential solutions to different challenges.
Keywords: Quantum mechanics; quantum theory; electrons photons; qubits.